Effect of Education and Income on Subjective Well-being of Adolescents - Kumari, Ruby; Srivastava, Ekta (Journal of Neonatal Surgery, 2025)
This study explores the effects of education and income on the subjective well-being (SWB) of adolescents in the Simanchal region of Bihar. Subjective well-being, comprising life satisfaction and emotional experiences (positive and negative affect), is a critical indicator of adolescent mental health. A sample of 272 school and college students participated in the study, and standardized measures such as the Life Satisfaction Scale and the SPANE were employed to assess SWB. Results from t-tests and two-way ANOVA analyses revealed that educational level significantly influenced all dimensions of subjective well-being, with secondary school students reporting higher life satisfaction and more positive affect than college students. Income, while significantly associated with both positive and negative affect, showed no significant effect on life satisfaction or affective balance. No interaction effects were observed between income and education, indicating that education had a more pronounced independent impact on adolescents’ subjective well-being. These findings highlight the role of education in shaping emotional and cognitive well-being during adolescence and suggest that policy efforts should prioritize educational support alongside economic interventions.